EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK HOMEROOM UNTUK MENINGKATKAN SELF DISCLOSURE ANAK PANTI ASUHAN - Br. Tarigan, Nabiilah; Chita Putri Harahap, Ade; Manurung, Purbatua (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2024)
Children in orphanages have difficulty establishing open communication with the environment. This is due to self-and-external factors, so it becomes an inhibiting factor in the process of children's self-development in orphanages. The purpose of this study was to find out: (1) the condition of children's self-openness in orphanages before and after being given group guidance services with homeroom techniques, and (2) the effectiveness of group guidance services with homeroom techniques in increasing children's self-disclosure in orphanages. The method in this study is quantitative with the type of pre-experimental research and the research design uses one group pretest-posttest design. Sampling in this study used purposive sampling techniques. This study had a study population of 30 children and the study sample was 8 children who had low self-disclosure at the Mamiyai Al-Ittihadiyah Medan Orphanage. The instrument used is the self-disclosure scale with the Likert scale model. The data collected were analyzed with non-parametric statistics using the Wilcoxon signed rank test and assisted through the SPSS program version 22. The results explained that the pretest score was 82 and the post-test was 129.75, which means that there is an increase in the self-disclosure of children in orphanages. Furthermore, it is supported by the results of the hypothesis test which shows that asymp.sig (2-tailed) of 0.012 which is below alpha 0.05 (0.012<0.05) which means that Ho's hypothesis is rejected and Ha is accepted. Based on the results obtained, it can be concluded that group guidance services with homeroom techniques are effective in increasing children's self-disclosure at the Mamiyai Al-Ittihadiyah Medan Orphanage